PENGEMBANGAN METODE FULLY SIMULTANEOUS UNTUK PENYELESAIAN STRONG VISCOUS-INVISCID INTERACTION PADA AIRFOIL DENGAN DISCONTINUOUS GALERKIN - Dhanika
Analysis and design of airfoil are one of the most important processes in the design of aerospace products. To be able analyze the flow around airfoil, Because of cost and time reason, a simple computational method is developed, Viscous-Inviscid Interaction. VII method is a method that divides the fluid domain into two parts, that is viscous domain and inviscid domain. Solutions of the viscous domain in the airfoil surface are computed by using integral boundary-layer equation. While solutions of the inviscid domain outside of the viscous domain are computed by using Laplace equation. In this research, the writer using Panel method to solve inviscid flow around an airfoil. While the method used to discretize the system of differential equations of boundary layer is Discontinuous Galerkin that good for solving hyperbolic differential equation. In this research, Fully Simultaneous interaction is also applied where velocity distribution and boundary layer parameters could be solved simultaneously to solve the separation problems of flow around an airfoil. The use of Fully Simultaneous interaction is still limited locally in each panel and shows that the singularity problem has been successfully overcome although it still cannot provide a smooth solutions of boundary layer and velocity.